2015
DOI: 10.1007/s12035-015-9392-y
|View full text |Cite
|
Sign up to set email alerts
|

The Deleterious Effects of Oxidative and Nitrosative Stress on Palmitoylation, Membrane Lipid Rafts and Lipid-Based Cellular Signalling: New Drug Targets in Neuroimmune Disorders

Abstract: Oxidative and nitrosative stress (O&NS) is causatively implicated in the pathogenesis of Alzheimer's and Parkinson's disease, multiple sclerosis, chronic fatigue syndrome, schizophrenia and depression. Many of the consequences stemming from O&NS, including damage to proteins, lipids and DNA, are well known, whereas the effects of O&NS on lipoprotein-based cellular signalling involving palmitoylation and plasma membrane lipid rafts are less well documented. The aim of this narrative review is to discuss the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 304 publications
(308 reference statements)
0
32
0
Order By: Relevance
“…3) [172–174]. Alteration of structure and fluidity of plasma membrane associated with lipid peroxidation could affect the organization and function of dendritic spines, signaling pathways, receptor trafficking, and localization [175]. Indeed, alterations in lipid trafficking and metabolism affect membrane fluidity and lipid homeostasis early in ApoE4 carriers [92, 137, 176, 177].…”
Section: Oxidative Stress and Synaptic Dysfunction In Alzheimer’s Dismentioning
confidence: 99%
“…3) [172–174]. Alteration of structure and fluidity of plasma membrane associated with lipid peroxidation could affect the organization and function of dendritic spines, signaling pathways, receptor trafficking, and localization [175]. Indeed, alterations in lipid trafficking and metabolism affect membrane fluidity and lipid homeostasis early in ApoE4 carriers [92, 137, 176, 177].…”
Section: Oxidative Stress and Synaptic Dysfunction In Alzheimer’s Dismentioning
confidence: 99%
“…However, from the perspective of this article, it should be emphasized that the activity of NKA is not just dependent on adequate supplies of ATP but is heavily influenced by the redox state of the intracellular and extracellular environment. Unsurprisingly, animal and human studies confirm that oxidative and nitrosative stress inhibits NKA activity in rat hippocampus and prefrontal cortex [253,254] and in patients with SZ and BPD [255,256]. A combination of oxidative stress would also appear to explain the downregulation of NKA activity seen in MDD, AD, and other neurodegenerative diseases (reviewed by [257]).…”
Section: Nutritional Ketosis Astrogliosis and Nka Functionmentioning
confidence: 97%
“…Briefly, several authors have also reported strong negative correlations between the extent of membrane lipid peroxidation and NKA activity in vivo in illnesses as diverse as cardiovascular disease, SZ, and BPD [255,256,261]. The relationship between increased membrane lipid peroxidation and increasing NKA dysfunction appears to be mediated by decreased membrane fluidity and PUFA content [260,262].…”
Section: Nutritional Ketosis Astrogliosis and Nka Functionmentioning
confidence: 97%
“…Mechanisms underpinning the detrimental effects of excessive ROS levels on synaptic function are underpinned by oxidation of cytosolic and membrane proteins and peroxidation of membrane lipids [243,244]. For example, several research teams have reported that lipid peroxidation in presynaptic membranes impedes fusion pore opening, thereby restricting SV exocytosis, resulting in the abnormal retention of SVs within presynaptic active zones [245,246].…”
Section: Oxidative Stress and The Development Of Synaptic Dysfunctionmentioning
confidence: 99%